Influences of shadow education on the ecology of education – A review of the literature - Luo, Jiahui; Chan, Cecilia Ka Yuk (Educational Research Review, 2022)
Shadow education, also widely known as private tutoring or supplementary education, has attracted increasing research attention in the past two decades. The global expansion of shadow education, as well as its penetration to different educational stages and social classes, are believed to have far-reaching implications for the overall educational landscape. However, despite a steadily growing body of literature, no study to date has systematically reviewed the influences of shadow education from an ecological perspective. Therefore, borrowing Bronfenbrenner's ecological systems theory, this paper aims to provide a comprehensive overview of how shadow education influences different levels of educational ecosystems (i.e. individuals, micro-, meso-, exo-, and macro-system). Based on 74 empirical studies published between 2000 and 2020, the review reveals complex influences exerted by shadow education on multiple systems (e.g., students, mainstream schooling, families, and larger socioeconomic structures), contributing to a more sophisticated understanding of this phenomenon. The paper then discusses how the rise of shadow education creates significant changes to the ecology of education in which it operates, and concludes with implications for future practice and research.
Keywords: Influence; Private tutoring; Supplementary education; Tutor; shadow Education